Resolving Quality Difference Between OEM and OBM Product: A Case Study of Kang Na Hsiung - Hu, Yung-Ning (2012)
In the past decade, more and more OEM companies have realised the importance the value of brand after the success of Acer was witnessed and therefore has planned to develop its OBM brand. However, some difficulties in terms of budget and experience involved in the transition process prompt these companies to adopt a parallel OEM and OBM strategy. Under a mixed system, some companies in practical found the difficulty to operate both two businesses with different philosophies well. The Taiwan-based company, Kang Na Hsiung (KNH), has faced an issue of product quality difference between the two businesses. A case study of KHN was conducted in this research. The research aims to investigate the problem of quality differences between OEM and OBM products and to propose suggestions for improvement based on the analysis results. This research will first identify the specific dimensions of the poor quality performance of the OBM products by conducting consumer survey investigating the perception towards product quality of different brand. Next, it is suggested to find the potential factors that cause the poor quality performance of its OBM products. Final, a suggested possible improvement will be proposed to the company with feasibility evaluation.